Impaired Autophagy and Defective Mitochondrial Function: Converging Paths on the Road to Motor Neuron Degeneration - Edens, Brittany M.; Miller, Nimrod; Ma, Yong-Chao (Frontiers in Cellular Neuroscience, 2016)
Selective motor neuron degeneration is a hallmark of amyotrophic lateral sclerosis (ALS). Around 10 percent of all cases present as familial ALS (FALS), while sporadic ALS (SALS) accounts for the remaining 90 percent. Diverse genetic mutations leading to FALS have been identified, but the underlying causes of SALS remain largely unknown. Despite the heterogeneous and poorly understood etiology, different types of ALS exhibit overlapping pathology and common phenotypes, including protein aggregation and mitochondrial deficiencies. Here we review the current understanding of mechanisms leading to motor neuron degeneration in ALS, as they pertain to disrupted cellular clearance pathways, ATP biogenesis calcium buffering and mitochondrial dynamics. Through focusing on impaired autophagic and mitochondrial functions, we highlight how the convergence of diverse cellular processes and pathways contributes to common pathology in motor neuron degeneration.